Innovative Arrhythmia Technologies - Hoyle, Brian (MD Conference Express, 2014)
This article discusses updates in arrhythmia technologies including the computational modeling of arrhythmia, left atrial appendage occlusion or exclusion devices, new noninvasive ablation technologies, as well as new lead designs, leadless systems, and sensors.